Book Review: Human Rights in the South Pacific – Challenges and Changes - Harwood, Catherine (Victoria University of Wellington Law Review, 2009)
This article is a book review of Sue Farran Human Rights in the South Pacific Challenges and Changes (Routledge-Cavendish, United States and Canada, 2009). Recent events in the Pacific highlighted the potentially precarious existence of human rights in some Pacific states and showed that a vigorous human rights debate is needed to further realise human rights. Farran's book in the South Pacific examines themes and tensions raised by rights in Pacific states that have common law as part of their legal frameworks. Farran ponders the notion of human rights with a view to increase awareness of their value and establish workable mechanisms to bolster human rights in the Pacific. While the text offers no definitive solution, it provides a platform of ideas from which meaningful discourse on human rights can spring. Not only is the book accessible and informative, it is also an important contribution to the continuing rights debate in the Pacific by raising awareness of human rights issues for and by Pacific people and providing tangible suggestions for change.